The Influence of Digital Competency and Leader Member Exchange on Performance Through organizational Commitment (Study on It Personnel of Sultra Regional Police) - Wisudawan Zakaria, Zukamdani; Takdir S, Dedy; Hatani, La; Hamid, Wahyuniati (Journal of Neonatal Surgery, 2025)
This study aims to analyze the influence of Digital Competence and Leader Member Exchange (LMX) on performance through organizational commitment in IT personnel of Polda Sultra. As the object of research, 137 IT personnel of Polda Sultra were involved to gain deeper insight into the dynamics of their performance. The analysis method used is SEM-PLS (Structural Equation Modeling - Partial Least Squares), which allows testing the relationship between variables simultaneously. The main findings in this study indicate that Digital Competence has a significant positive influence on organizational commitment. This indicates that the higher the level of Digital Competence possessed by IT personnel of Polda Sultra, the stronger their commitment to the organization. Knowledge and skills in the digital field, such as the use of sophisticated hardware and software, play a key role in increasing personnel engagement with the mission and goals of the organization. Furthermore, Leader Member Exchange (LMX) was also found to have a positive influence on organizational commitment, which in turn improves performance. Effective communication and positive working relationships between leaders and team members have been shown to play an important role in creating mutual trust and job satisfaction. Overall, this study shows that strengthening Digital Competence and the quality of LMX relationships can strengthen organizational commitment, which ultimately contributes to improving the performance of IT personnel at Polda Sultra. This study suggests that leaders need to focus on improving digital competence and building better relationships between leaders and members to achieve organizational goals optimally.